The Spending and Absorption of Aid in PRGF Supported Programs - Martijn, Jan (IMF Working Papers; Working Paper, 2008)
This paper studies the spending and absorption of aid in PRGF-supported programs, verifies whether the use aid is programmed to be smoothed over time, and analyzes how considerations about macroeconomic stability influence the programmed use of aid. It finds that PRGF-supported programs allow countries to use most or almost all increases in aid within a few years. The paper finds some evidence that the programmed absorption of aid is higher in countries where reserve coverage is above a certain threshold, whereas programmed spending does not seem to depend on inflation. Finally, it shows that the presence of a PRGFsupported program does not constrain the actual spending and absorption of aid.